Zernike Moments Description of Solar and Astronomical Features: Python Code - Hossein Safari; Nasibe Alipour; Hamed Ghaderi; Pardis Garavand (Iranian Journal of Astronomy and Astrophysics)
Due to the massive increase in astronomical images (such as James Web, Solar Dynamic Observatory, and Solar Orbiter), automatic image description is essential for solar and astronomical. Zernike moments (ZMs) are unique due to the orthogonality and completeness of Zernike polynomials (ZPs); hence, ZMs are valuable for converting a two-dimensional image to a one-dimensional series of complex numbers. The magnitude of ZMs is rotation invariant, and by applying image normalization, scale and translation invariants can be made, which are helpful properties for describing solar and astronomical images. The lower-order ZMs express the overall shape of the objects of an image, and the higher-order ZMs provide more details of the objects and delicate structures within an image. In this Python package, available at GitHub and PyPI, we describe the characteristics of ZMs via several examples of solar (large and small scale) features, astronomical, and human face images. These independent and unique properties of ZMs can describe the structure and morphology of objects in an image. Hence, ZMs are helpful in machine learning to identify and track the features of several.